Exploring Gen Z Students Experiences of Spotify Use in Listening Practice - Anindia Hena Fitriana; Susiati Subari (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study examines the methods employed by Gen Z students in English Language Education program to practice listening to English songs through Spotify as a learning tool. It specifically investigates how they listen, how they learn, and how they perceive the impact of this habit on their vocabulary, listening comprehension, and pronunciation.Methodology: This study seeks to examine a qualitative descriptive method with open-ended interviews involving 20 Gen Z students (cohort 2024-2025) who regularly use Spotify for practicing listening to English songs. Interview data were audio-recorded, then transcribed verbatim and analyzed thematically to identify recurring patterns in students’ listening routines, repeated listening habits, vocabulary learning strategies, and perceived impacts while learning through Spotify. Results: The findings demonstrate that students incorporate Spotify into their daily routines (e.g., during commutes, studying, or household chores) and participate in repeated listening to progress from mere melody recognition to understanding narrative meanings, expressions, and vocabulary definitions within song lyrics. Some strategies are reading the lyrics, using AI and translation tools, and taking notes.Applications/Originality/Value: This study contributes to Spotify as a self-regulated learning environment where students appropriate commercial streaming platforms for educational purposes. It proposes integrating playlist-based assignments and lyric-focused vocabulary journals into formal instruction to effectively bridge students’ informal digital practices with academic language learning objectives.